KAJIAN TRADISI LISAN DALAM UPACARA ADAT ETNIK SIMALUNGUN TERHADAP KERJA KERAS DAN GOTONG ROYONG - Damanik, Dwi Azri; Ritonga, Sakti (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2025)
Oral tradition is an important part of intangible cultural heritage that has educational and social functions within society. In the context of the Simalungun ethnic community, oral traditions such as Umpasa and social practices like Marhobas and Marharoan Bolon not only strengthen cultural identity but also transmit values of hard work and mutual assistance across generations. This research employs a qualitative approach using interviews, observation, and documentation techniques. The results indicate that oral traditions serve as an effective character education tool, despite facing challenges from modernization. Preservation efforts such as digitalization and education based on local wisdom are crucial for maintaining the existence of this culture.